Comparison of Tocilizumab and Anakinra in the Treatment of COVID-19: A Single-Center Experience - Bengisu Pınar Acat; Ahmet Tezce; Özben Çavdar; Murat Acat (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: The aim of this study was to examine whether a difference between endotracheal intubation, non-invasive mechanical ventilation, high flow oxygen therapy requirements and 28-day mortality rate in severe and critical coronavirus disease 2019 (COVID-19) patients receiving anakinra and tocilizumab treatment. Material and Methods: A total of 70 patients infected with COVID-19, who were treated with tocilizumab and anakinra from April 2020 to March 2021 at Karabük Training and Research Hospital, were recruited in this retrospective study. Data on patient demographics, comorbidities, treatments, clinical outcomes of the patients’ and hemogram findings were retrieved from hospital records. Results: The mean age of the patients was 61.34±11.8 years. Of the 70 patients, 12 (17.1%) were female and 58 (82.9%) were male. Severe and critical COVID-19 cases were evident in 48 (68.6%), and 22 (31.4%) patients, respectively. The mortality rate in 28 days was not statistically significantly different between the tocilizumab and anakinra groups (p=0.999). Both the necessity of high flow oxygen therapy and non-invasive mechanical ventilation were lower in the tocilizumab group than in the anakinra group (p<0.001, and p=0.002, respectively), while there was no statistically significant difference in the necessity of intubation between the two groups (p=0.999). The length of stay was also significantly shorter in the tocilizumab group (p=0.027). Conclusion: High flow oxygen therapy, non-invasive mechanical ventilation requirements, and length of stay were significantly lower than anakinra in the tocilizumab group. Excessive inflammatory response with cytokine storm features causes severe disease course and worsens prognosis in COVID-19.